Cell cycle deregulation by methyl isocyanate: Implications in liver carcinogenesis. Issue 3 (5th January 2012) - Panwar, Hariom; Raghuram, Gorantla V.; Jain, Deepika; Ahirwar, Alok K.; Khan, Saba; Jain, Subodh K.; Pathak, Neelam; Banerjee, Smita; Maudar, Kewal K.; Mishra, Pradyumna K.
<x xml:space="preserve">Abstract</x> Liver is often exposed to plethora of chemical toxins. Owing to its profound physiological role and central function in metabolism and homeostasis, pertinent succession of cell cycle in liver epithelial cells is of prime importance to maintain cellular proliferation. Although recent evidence has displayed a strong association between exposures to methyl isocyanate (MIC), one of the most toxic isocyanates, and neoplastic transformation, molecular characterization of the longitudinal effects of MIC on cell cycle regulation has never been performed. Here, we sequentially delineated the status of different proteins arbitrating the deregulation of cell cycle in liver epithelial cells treated with MIC. Our data reaffirms the oncogenic capability of MIC with elevated DNA damage response proteins pATM and γ‐H2AX, deregulation of DNA damage check point genes CHK1 and CHK2, altered expression of p53 and p21 proteins involved in cell cycle arrest with perturbation in GADD‐45 expression in the treated cells. Further, alterations in cyclin A, cyclin E, CDK2 levels along with overexpression of mitotic spindle checkpoints proteins Aurora A/B, centrosomal pericentrin protein, chromosomal aberrations, and loss of Pot1a was observed. Thus, MIC impacts key proteins involved in cell cycle regulation to trigger genomic instability as a possible mechanism of developmental basis of liver carcinogenesis. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 284–297, 2014.